Viewing faculty development through an organizational lens: Sharing lessons learned. - Kolomitro, Klodiana; Hamilton, Joanne; Leslie, Karen; Hazelton, Lara; Veerapen, Kiran; Kelly-Turner, Kenna; Keegan, David (Medical Teacher, 2021)
Faculty Development (FD) plays a key role in supporting education, especially during times of change. The effectiveness of FD often depends upon organizational factors, indicating a need for a deeper appreciation of the role of institutional context. How do organizational factors constrain or enhance the capacity of faculty developers to fulfil their mandates? Using survey research methodology, data from a survey of FD leaders at Canadian medical schools were analyzed using Bolman and Deal's four frames: Symbolic, Political, Structural, and Human Resource (HR). In the Symbolic frame, FD leaders reported lack of identity as a FD unit, which was seen as a constraining factor. Within the Political frame, developing visibility was seen as an enhancing factor, though it did not always ensure being valued. In the Structural frame, expanding scope of practice was seen as an enhancing factor, though it could also be a constraining factor if not accompanied by increased resources. In the HR frame, a sense of instability due to changing leadership and uncertainty about human resources was seen as a constraining factor. While broadening the mandate of FD can generally be considered as positive, it is imperative that it is appropriately resourced and accompanied by recognition of FD as a valued contributor to the educational mission.